Synthesis and Characterization of P(NIPAAm-co-AAc) Hydrogels with L-Lysine-cross-linker - Yu, Yueqin; Tian, Hongjie; Chang, Xianzhi (Asian Journal of Chemistry, 2010)
In order to improve the biocompatibility of the hydrogels, hydrogels composed of N-isopropylacrylamide (NIPAAm) and acrylic acid (AAc) were prepared by redox polymerization with L-lysine-cross-linker. L-lysine-cross-linker was synthesized by the acrylation of the amino groups of the L-lysine and characterized by 1H NMR. With L-lysine-cross-linker, loosely cross-linked poly(N-isopropylacrylamide-co-acrylic acid) [P(NIPAAm-co-AAc)] hydrogels were synthesized in phosphate-buffered saline (PBS, pH = 7.4 ± 0.1) and their phase transition behaviour, low critical solution temperature (LCST), water content were investigated. The LCST could be adjusted at 35-38 ºC by changing the hydrogel's composition. The hydrogels contained more than 90 % water content at 37 ºC in the ultra pure water and have a prospective swelling in the PBS (> 84.72 %), which was controlled by the molar ratio of NIPAAm/AAc, swelling media and cross-linking density. This L-lysine-cross-linked P(NIPAAm-co-AAc) hydrogels which can be tailored to create environmentallyresponsive artificial extracellular materials will have a potential use in the future.